FACTORS INFLUENCING PRODUCTIVITY IN WORKING FROM HOME IN A SELECTED MULTINATIONAL FIRM - Muhammad Haziq Ridzuan (Tesis, 2021)
The main objective of this research is to examine factors affecting productivity when working from home among employees in a selected pharmaceutical multinational corporation in Kuala Lumpur.